Die Krisensituation der nordeuropäischen Holzindustrie in der zweiten Hälfte der siebziger Jahre in Abhängigkeit von konjunkturellen Schwankungen und Strukturproblemen - Windhorst, Hans-Wilhelm (ERDKUNDE, 1981)
The paper presents results of a research programme undertaken by the author within the special industrial geography programme of the German Research Foundation. The main goal of the article is to show which factors led to the critical economic situation in the wood processing industries of Finland and Sweden in the second half of the seventies, how the critical situation developed, and by which means it might be overcome. In part 2 the structure of Finland's and Sweden's forestry and wood processing industries is presented in an overview. It is obvious that the recession led to a rapid decline of the annual removals and by this to an accumulation of cutable roundwood. The critical phase in the economic development also led to an important decline in the contribution of forestry and forest products industries to the gross national product and the foreign trade of these countries, while the United States and Canada could increase their exports to Europe because of lower roundwood prices, lower wages, and a very favourable exchange rate. In part 3 first indicators of the crisis are presented (unemployment, closedowns of factories, changes in the ownership of vertically integrated companies); there then follows an analysis of the factors that had the most important influence on the origin of the crisis (roundwood prices, wages, situation on the world market for wood products, political decisions, liabilities of the wood processing industries, lack of concomitant research). Part 4 shows the economic and social problems which came up and the means by which the structural problems of the wood processing industries could be overcome.